miRNome Reveals New Insights Into the Molecular Biology of Field Cancerization in Gastric Cancer - Pereira, Adenilson; Moreira, Fabiano; Vinasco-Sandoval, Tatiana; Cunha, Adenard; Vidal, Amanda; Ribeiro-dos-Santos, André M.; Pinto, Pablo; Magalhães, Leandro; Assumpção, Mônica; Demachki, Samia; Santos, Sidney; Assumpção, Paulo; et al. (Frontiers in Genetics, 2019)
Background: MicroRNAs (miRNAs) play an important role in gastric carcinogenesis and have been associated with field cancerization in gastric cancer; however, the role of these molecules is not fully understood in this process. We performed miRNome sequencing of non-cancer, adjacent to tumor and gastric samples, to understand the involvement of miRNAs in gastric field cancerization. Methods: We analyzed samples of patients without cancer as control (non-cancer) and adjacent to cancer and gastric cancer paired samples, and consider |log2(fold change)|>2 and P-value<0.05 as a parameter. We also evaluated the biomarkers potential of the studied miRNAs by using receiver operating characteristic (ROC) and the area under curve (AUC>0.85). Results: We found fifteen miRNAs exclusively deregulated in gastric cancer, of which six have potential diagnostic value for advanced disease. Eleven were deregulated exclusively in adjacent tissue, with ten up-regulated tumor suppressors (TS-miRs). Of these, five have potential diagnostic value for the early stages of gastric cancer. The functional analysis of these TS-miRs demonstrates that they regulate important cellular signaling pathways (PI3K-Akt, HIF-1, Ras, Rap1, ErbB and MAPK signaling pathways), that are involved in gastric carcinogenesis. Five miRNAs were differentially expressed in both gastric cancer and adjacent regarding to non-cancer tissues; among them, hsa-miR-200a-3p and hsa-miR-873-5p have potential diagnostic value for early and advanced stages of the disease. Only hsa-miR-196-5p was differentially expressed between adjacent to cancer and gastric cancer tissues. In addition, the other miRNAs identified in this study were not differentially expressed between adjacent to cancer and gastric cancer, suggesting that these tissues are very similar and that share these changes. Conclusion: Our results show that gastric cancer and adjacent tissues have an expression profile for miRNAs analyzed very similar, indicating that miRNAs studied are intimately associated with field cancerization in gastric cancer. The overexpression of TS-miRs in adjacent tissue is likely an antitumor mechanism. Additionally, these miRNAs have great accuracy in discriminating non-cancer from other tissues and can be potentially useful as biomarkers for gastric cancer.